The influence of household head’s skill level and digital agricultural outreach on farmers’ adoption of conservation tillage technology: an empirical study based on northwestern China - Ding, Xiuling; Li, Lipeng; Lu, Qian; Bai, Chongfan (Frontiers in Sustainable Food Systems, 2025)
IntroductionIn the digital economy era, aligning farmers’ skill levels with advanced technologies is crucial for advancing agricultural informatization, and exploring the interaction between skill levels and digital promotion holds important policy value for optimizing conservation tillage technology extension strategies.MethodsThis study utilizes survey data from 487 farm households in Shanxi and Shaanxi provinces, which are important melon and fruit-producing regions in Northwest China, constructs a composite skill index, and employs a binary probit model to examine the impact of skill levels and digital promotion on the adoption of conservation tillage technologies.ResultsThe findings show that higher skill levels significantly increase the adoption probability of subsoiling, integrated pest management (IPM), and organic fertilizer application. In terms of digital tools, mobile phone usage significantly promotes the adoption of subsoiling, IPM, and organic fertilizer, while computer usage only has a significant impact on organic fertilizer adoption. Additionally, digital promotion plays an intermediary role in the relationship between skill levels and technology adoption, and there is a substitution effect between mobile phone and computer usage in promoting the adoption of IPM, organic fertilizer, and straw mulching.Discussion and insightsThese results provide policy insights: differentiated promotion of digital tools based on their functional characteristics, targeted support for elderly farmers to bridge the digital divide and strengthened synergy between skills and digital tools can effectively enhance the penetration of conservation tillage technologies, which is of great significance for advancing agricultural green development and narrowing the urban-rural digital gap.